Anthropometric standardisation and quality control protocols for the construction of new, international, fetal and newborn growth standards: the INTERGROWTH‐21st Project. (11th July 2013) - Cheikh Ismail, L; Knight, HE; Ohuma, EO; Hoch, L; Chumlea, WC; ,
Abstract : The primary aim of the INTERGROWTH‐21 st Project is to construct new, prescriptive standards describing optimal fetal and preterm postnatal growth. The anthropometric measurements include the head circumference, recumbent length and weight of the infants, and the stature and weight of the parents. In such a large, international, multicentre project, it is critical that all study sites follow standardised protocols to ensure maximal validity of the growth and nutrition indicators used. This paper describes in detail the anthropometric training, standardisation and quality control procedures used to collect data for these new standards. The initial standardisation session was in Nairobi, Kenya, using newborns, which was followed by similar sessions in the eight participating study sites in Brazil, China, India, Italy, Kenya, Oman, UK and USA. The intraobserver and inter‐observer technical error of measurement values for head circumference range from 0.3 to 0.4 cm, and for recumbent length from 0.3 to 0.5 cm. These standardisation protocols implemented at each study site worldwide ensure that the anthropometric data collected are of the highest quality to construct international growth standards.